Penguatan Kesadaran Ekoteologi Melalui Strategi Pendidikan Agama Kristen Di Era Digital Untuk Mengatasi Strategi Krisis Energi Dan Kerusakan Lingkungan - Sakey, Jenet Selfiani; S. Silahi, Lila; Losando, Richard; Hia, Epi Edukaisen (JDP (JURNAL DINAMIKA PENDIDIKAN), 2025)
The waste crisis does not only occur because it is caused by fossils, but with the development of civilization, environmental damage is also influenced by human lifestyles related to the internet. Human life, which cannot be separated from the internet, turns out to have an influence on the environment. Digital waste is often ignored by society due to the lack of ecological literacy. Through this research, it is hoped that society will have comprehensive ecotheological awareness so that they can take wise actions in interacting with the internet. The method used uses qualitative exploration. This method is used to explore and discover new environmental problems that the general public is not aware of. This research shows that ecotheological awareness in the digital space today needs to remember the problem of digital waste which many people are not aware of. Efforts to transform awareness into an alternative preventive effort that can prevent further energy crises.